The trouble with cowboys : a big sky romance - Hunter, Denise, 1968- (Hunter, Denise, 1968- Big sky romance., 2012)
"Only one pair of boots--and the cowboy wearing them--can get Annie out of the mess she's in. Annie Wilkerson is Moose Creek's premiere horse trainer and equine columnist for Montana Living. Money is tight as she tries to put her kid-sister through college and provide for her young nephew. When Annie's column is cancelled, she's given first shot at a new lovelorn column--and she can't afford to turn it down. Only problem is . . . Annie's never been in love. Always resourceful, she reluctantly strikes a deal with the town's smooth-talking ladies' man Dylan Taylor: She'll work with his ailing horse, Braveheart, if he'll help her answer the reader letters. Working closely with Dylan is harder than Annie imagined, and she quickly realizes she may have misjudged him. But her unwavering conviction that cowboys are nothing but trouble has kept her heart safe for years. And she can't risk getting hurt now. The more Annie tries to control things, the more they fall apart. Her feelings are spinning out of control, and her sister's antics are making life increasingly more difficult. Annie knows she needs to turn the reins over to God, but surrender has never come easily. When Dylan reveals his feelings for her, Annie doesn't know what to trust--her head or her heart. The trouble with this cowboy is that he might just be exactly what she needs."--P. [4] of cover.